2006
DOI: 10.1002/col.20207
|View full text |Cite
|
Sign up to set email alerts
|

Recognized visual space of illumination: No simultaneous color contrast effect on light source colors

Abstract: Previous study [Cunthasaksiri et al., Color Res Appl 2004;29:255-260] showed that simultaneous color contrast (SCC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Originally, Katz15 was the first to classify the colors of objects in terms of “modes of color appearance.” He described and compared 11 modes of appearance. However, in this study, we classified the color appearance mode into three obvious modes based on the recognized visual space of illumination theory 16–21. First, a color can be perceived as a property of a surface when its luminance level is quite low.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Originally, Katz15 was the first to classify the colors of objects in terms of “modes of color appearance.” He described and compared 11 modes of appearance. However, in this study, we classified the color appearance mode into three obvious modes based on the recognized visual space of illumination theory 16–21. First, a color can be perceived as a property of a surface when its luminance level is quite low.…”
Section: Introductionsupporting
confidence: 93%
“…However, in this study, we classified the color appearance mode into three obvious modes based on the recognized visual space of illumination theory. [16][17][18][19][20][21] First, a color can be perceived as a property of a surface when its luminance level is quite low. Second, it is perceived as a property of light source or light itself (i.e., self-radiating) when its luminance level is adequately high.…”
Section: Introductionmentioning
confidence: 99%
“…In psychophysical studies, Ikeda and his colleagues investigated the effect of surrounding surface colors on the color appearance of a high-luminance test patch in the illuminantcolor mode [21][22][23]. They measured the color appearance of a test patch in a natural scene with variable illuminations, and the results showed that color constancy gradually failed for the high-luminance test patch when the luminance became too high for it to appear as a natural object color [22].…”
Section: Past Studies Testing the Influence Of Color Appearance Onmentioning
confidence: 99%